2019
DOI: 10.9734/ejnfs/2019/v10i430120
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Bread Produced from Wheat and White Kidney Bean Composite Flour

Abstract: Aim: To evaluate the Quality characteristics of Bread produced from Wheat and Kidney Bean composite flour blend. Study Design: Composite bread was produced from wheat and kidney bean flour of various proportions (10, 15, 20 and 25%). Proximate (protein, ash, moisture, fibre, fat and carbohydrate) composition, functional (Bulk density, foaming capacity, swelling index, water absorption capacity and oil absorption capacity) properties and sensory (appearance, taste, flavour, texture and overall acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 12 publications
(19 reference statements)
5
23
1
Order By: Relevance
“…The basic indicators of the baking quality of triticale bread, such as dough yield, oven loss and bread‐making performance, were calculated along with the physicochemical bread quality indicators, which were determined 24 hr after baking (Ukeyima et al., 2019). The volume of 100 g of bread was calculated after weighing and measuring the volume of loaves using a Sa‐Wa apparatus (Sadkiewicz Instruments, Bydgoszcz, Poland) according to AACC Method No.…”
Section: Methodsmentioning
confidence: 99%
“…The basic indicators of the baking quality of triticale bread, such as dough yield, oven loss and bread‐making performance, were calculated along with the physicochemical bread quality indicators, which were determined 24 hr after baking (Ukeyima et al., 2019). The volume of 100 g of bread was calculated after weighing and measuring the volume of loaves using a Sa‐Wa apparatus (Sadkiewicz Instruments, Bydgoszcz, Poland) according to AACC Method No.…”
Section: Methodsmentioning
confidence: 99%
“…These flours contain almost double the total protein compared to MF. Recently, Aquino-Bolaños et al [31] determined that the protein content in P. vulgaris green beans exists in a range of 7 to 12%, much lower than the values obtained in GBF; nonetheless, the protein values in white beans are 36.5-37.1% [7]. This value is close to the one obtained for GBF.…”
Section: Proximal Analysis Of Floursmentioning
confidence: 59%
“…There is not much information about the nutritional content of green beans. The authors reported ash values that ranged from 3-4.4% in white kidney beans [7,8]. Concerning MF, some of the most studied mesquite species are P. alba, P. nigra, P. pallida, P. chilensis, P. cineraria, P. tamarugo, and P. juliflora [9].…”
Section: Proximal Analysis Of Floursmentioning
confidence: 99%
See 1 more Smart Citation
“…They contributed 65.79% of the total variance when the extraction method was performed in PCA. Ivanovski et al, 2012;Kure et al, 2021;Malavi et al, 2022;Otegbayo et al, 2018;Ukeyima et al, 2019). These breads are an option for people interested in variety, heavier meals and nutrition.…”
Section: Descriptive and Consumer Testsmentioning
confidence: 99%